2019
DOI: 10.3390/rs11151745
|View full text |Cite
|
Sign up to set email alerts
|

Potato Yield Prediction Using Machine Learning Techniques and Sentinel 2 Data

Abstract: Traditional potato growth models evidence certain limitations, such as the cost of obtaining the input data required to run the models, the lack of spatial information in some instances, or the actual quality of input data. In order to address these issues, we develop a model to predict potato yield using satellite remote sensing. In an effort to offer a good predictive model that improves the state of the art on potato precision agriculture, we use images from the twin Sentinel 2 satellites (European Space Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(68 citation statements)
references
References 79 publications
(86 reference statements)
2
66
0
Order By: Relevance
“…However, more suitable algorithms were found and kernel-based extreme learning machine (KELM) generally performed the best (49 and 57 out of 100 repetitions for reflectance and first derivative spectra, respectively) for estimating the chlorophyll content when assessed using the ratio of performance to deviation (RPD) values. Although SVM's robustness has been reported in some studies [59][60][61], and it performed best in 20 and 37 of the repeats, it also showed the worst performance in 28 and 33 repetitions for the reflectance and first derivative spectra, respectively. These results strongly suggest that SVM is not a stable method.…”
Section: Performance Of Different Machine Learning Algorithmsmentioning
confidence: 87%
“…However, more suitable algorithms were found and kernel-based extreme learning machine (KELM) generally performed the best (49 and 57 out of 100 repetitions for reflectance and first derivative spectra, respectively) for estimating the chlorophyll content when assessed using the ratio of performance to deviation (RPD) values. Although SVM's robustness has been reported in some studies [59][60][61], and it performed best in 20 and 37 of the repeats, it also showed the worst performance in 28 and 33 repetitions for the reflectance and first derivative spectra, respectively. These results strongly suggest that SVM is not a stable method.…”
Section: Performance Of Different Machine Learning Algorithmsmentioning
confidence: 87%
“…Currently S2 can provide imagery every five days under ideal circumstances, which facilitates characterizing the entire crop life cycle at high temporal resolution. Some studies have utilized and validated the potential for using S2 for land cover classification [30], crop mapping [31,32], canopy chlorophyll and nitrogen content quantification [33,34] and yield estimation of other crops, with reasonable success [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Early detection and crop management associated with yield limitations can help increase productivity [4,23,80]. Crop yield prediction models could aid in early decision-making, optimizing the time required for eld evaluation, thus reducing the resources allocated to the research programs [81]. Furthermore, the predicted yield maps could also be used to implement variable rate technology (VRT) systems in spatial databases, thereby accomplishing precise eld-level inputs through the entire eld [82].…”
Section: Cassava Root Yield Predictions Using ML Modelsmentioning
confidence: 99%
“…Remote sensing approaches can provide growers with nal yield assessments and show variations across the eld [79]. In remote sensing, MS imagery can describe crop development for potato tuber yield forecasting, across time and space, in a cost-effective manner [81,82].…”
Section: Cassava Root Yield Predictions Using ML Modelsmentioning
confidence: 99%